The concept of evil in Judaism, Christianity and Islam - Rachik, Catharina; Tamer, Georges 1960-; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2025)
"The present volume of the series Key Concepts in Interreligious Discourses explores various conceptions of evil in Judaism, Christianity, and Islam, including key terms from their respective sacred texts, major theodicy discussions and contemporary developments. Throughout history and even today, religious scholars and believers have struggled with the question of the origin of evil and how a benevolent God can allow evil to exist in the world. Why does a compassionate God not prevent deadly diseases or natural disasters? What do religions define as evil, and is God responsible for or even the creator of this evil? The articles, written by distinguished scholars in their respective fields, offer a variety of answers to such existential questions. The articles address topics such as the origin of evil, the responses to evil in sacred texts and religious traditions, and the role of human agency. Each author offers a critical analysis of these topics as well as recommendations for future research. The volume also highlights commonalities and differences among the three monotheistic religions."--Publisher's website
Keywords: Good and evil -- Religious aspects; Theodicy; Théodicée; Konferenzschrift -- 2020 -- Erlangen